2008
DOI: 10.1088/0268-1242/23/7/075003
|View full text |Cite
|
Sign up to set email alerts
|

Programme and retention characteristics of SONOS memory arrays with layered tunnel barrier

Abstract: Layered tunnel barriers (T-ONO) might help circumvent retention limitations of nitride charge trapping devices (SONOS) programmed/erased by direct tunnelling without invoking high-K dielectrics in the gate stack. In order to establish to what extent the properties of a T-ONO tunnel layer influence the performance of SONOS memories, NOR memory arrays containing a silicon oxide/silicon nitride/silicon oxide T-ONO layer, a silicon nitride charge trapping layer and a silicon oxide blocking layer were fabricated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The engineered ONO structure, referred to as the variable oxide thickness (VARIOT) tunnel barrier, exhibited notable sensitivity to the electric field generated by the gate bias [48,49]. When the energy level of the electrons within the silicon channel was lower than that of the potential barrier, the ONO barrier functioned as an obstacle to electron penetration [50][51][52][53]. However, a substantial electric field induced significant band bending within the ONO barrier, allowing the electron wavefunction to tunnel through the thin triangular potential barrier.…”
Section: Evaluation Of the Multi-functional Charge-trap-flash-type Fi...mentioning
confidence: 99%
“…The engineered ONO structure, referred to as the variable oxide thickness (VARIOT) tunnel barrier, exhibited notable sensitivity to the electric field generated by the gate bias [48,49]. When the energy level of the electrons within the silicon channel was lower than that of the potential barrier, the ONO barrier functioned as an obstacle to electron penetration [50][51][52][53]. However, a substantial electric field induced significant band bending within the ONO barrier, allowing the electron wavefunction to tunnel through the thin triangular potential barrier.…”
Section: Evaluation Of the Multi-functional Charge-trap-flash-type Fi...mentioning
confidence: 99%
“…A representative set of data storage technology has been considered with three main groups: Standard RAM (Flash, [104,105] DRAM: dynamic random access memory, [106,107] PCM: Phasechange memory, [108,109] STT-MRAM: spin-transfer torque magnetoresistive random-access memory [110,111] ), inorganic ReRAM [112][113][114][115][116][117] and MOF-based ReRAM. [66,68,71,118] In most of the studies the storage density at laboratory scale is indicated.…”
Section: Sustainabilitymentioning
confidence: 99%
“…With conventional floating gate type nonvolatile memories approaching their scaling limits, the polysilicon-oxide-nitrideoxide-silicon (SONOS) charge trap flash (CTF) memory has recently drawn attention for applications in the nonvolatile memory market due to the advantages of lower programming voltage, compatibility with standard complementary metal oxide semiconductor technology, and better endurance characteristics for memory operation [1,2]. The SONOS device is also one of the most promising candidates to realize the continuous vertical scaling of flash memories through the mechanism of charge storing in discrete traps [3][4][5]. However, the trade-off between data retention and program/erase speed is the main bottleneck for SONOS devices in replacing floating-gate ones [6].…”
Section: Introductionmentioning
confidence: 99%